Diagnosis and management of chronic osteomyelitis and cemento-osseous dysplasia of the mandible. (2nd December 2019) - Akram, Arifa; Lidhar, Tajinder; Valentine, Katy Marie; Webb, Roger
Abstract : Chronic osteomyelitis is a severe and persistent infection of the bone including the bone marrow. Cemento-osseous dysplasias are a group of conditions arising from the periodontal ligament tissue and are categorized into peri-apical, focal and florid. A case of a patient with buccal and submandibular swelling associated with a discharging sinus between LR45 was presented. History, examination and investigations confirmed a diagnosis of chronic osteomyelitis and an incidental finding of florid cemento-osseous dysplasia of the mandible. The patient's treatment is discussed within the context of important clinical considerations required in managing these patients. CPD/Clinical Relevance: It is pertinent for a general practitioner to be aware of signs and symptoms associated with chronic osteomyelitis and understand the management options.